"Reality is chaotic": the New American Juridical Realism between universalism and relativism of human rights (Società e diritti, 2018)
The Universal Declaration of Human Rights has fueled an intense theoretical discussion between two opposite poles: on one side, the defendants of the universalism and, on the other side, the supporters of cultural relativism. Indeed, the former scholarship have explained many relevant theories in order to find a moral basement for the human rights global expansion, whereas the latter trend have always asserted that the entire system of human rights law is a “gift from the West” and, for that reason, unenforceable all over the world.  However, today it is impossible to discuss about this issue without an empirical approach that, starting from an “on ground” studies, allows us to understand the real way through the international provisions are applied to the dissimilar socio-legal contexts of destination.  The research proposal of New Legal Realism confirms this kind of purpose and, thanks to its methodology, currently embodies an effective tool to deeply understand the complexity of the so called human rights practice and to analyze, from a critical point of view, both universalist and relativist thesis.Key words: New Legal Realism, Empiricism, Human Rights, Universalism, Cultural Relativism